Material samples, mock up, test report and technical specification of sealer, putty and emulsion with the reply of BRACU NCP Engineering team (RFA-442_Rev B) - BUCG-ABC Joint Venture (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.